Low-Profile Array of Wire Patch Antennas - H. Zhang; R. Chantalat; F. Torres; M. Thevenot; T. Monediere; B. Jecko (International Journal of Antennas and Propagation)
A low-profile antenna over a ground plane that radiates a directive lobe in the end fire direction is described in this paper. An array of 16 wire patch antenna (WPA) fed by an integrated 16 ways power divider has been designed. Owing to its low height, low cost, high robustness, and monopolar radiation pattern, the WPA has been chosen as unit cell of the array that must be placed on the vehicle roof. A gain higher than 18.9 dB was achieved in the end fire direction over a 4.5% bandwidth. However, the antenna has been tilted in order to compensate the beam deviation caused by the edge diffraction. Moreover, a vertical metallic plane has been inserted to eliminate the back fire radiation. Its position and the disposition of the WPAs are explained in this paper. A prototype with four elements has been manufactured in order to validate the antenna principle. A gain difference lower than 0.5 dB is achieved between the measurements and the simulations.